Spontaneous nontraumatic epidermoid cyst of the clitoris: a rare case report - Nayak, Arun; Sarmalkar, Meenal; Mehendale, Madhuri; Shah, Shrutika (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Epidermoid cysts are slow growing, intradermal or subcutaneous tumors with a wall composed of true epidermis. They are rarely seen in the clitoral region but when found; they are commonly seen following female genital mutilation. Spontaneous onset clitoral epidermoid cysts have been scarcely reported .We report a rare case of a large spontaneous nontraumatic epidermoid cyst of clitoris in a 22 year old nulliparous female. This presentation mimicked clitoromegaly but was diagnosed to be a large epidermoid cyst after excision.